Understanding community in synchronous online learning: do perceptions match behaviours?. (3rd May 2020) - Çakıroğlu, Ünal; Kılıç, Servet
ABSTRACT: The community of inquiry (CoI) framework is becoming increasingly popular in online learning. The relationships among CoI constructs (cognitive, teaching and social presences) were generally investigated through surveys. However, some methodological challenges were noticed in CoI studies such as the limitations in data diversity or data verification. Hypothesising that learners' perceptions about CoI constructs may not reflect their actual behaviours, this study matches students' perceptions and actual behaviours reflecting the CoI constructs in an online learning setting in a synchronous online undergraduate programme. Data from CoI surveys, online discussion records and observations were comparatively discussed. The results indicated that relationships between the behaviours and perceptions about CoI constructs were quite positive and students' perceptions about CoI constructs almost matches with their actual behaviours. Thus, the study confirmed the power of determining the interactions reflecting CoI constructs in online learning within CoI surveys. It is hoped that the study may shed a light with its contribution in providing some evidence for the question of whether conventional data collection techniques in CoI studies is required to be revisited or not.